Correlation between atmospheric pressure changes and abdominal aortic aneurysm rupture : results of a single-center study - Molacek, Jiri; Treska, Vladislav; Kasik, Miroslav; Houdek, Karel; Baxa, Jan (Surgery today (Tokyo, Japan), 2013)
Purpose There is much interest in all factors that influence the etiopathogenesis of abdominal aortic aneurysm (AAA) rupture. Apart from the well-established factors such as arterial hypertension, smoking, age, and genetic predisposition, less common factors that may play a role in the mechanism of the rupture are the subject of much discussion. These include atmospheric conditions, temperature, and atmospheric pressure. We conducted this study to investigate the effects of the absolute value of atmospheric pressure and its changes on the frequency of AAA rupture. Methods We retrospectively examined 54 patients who underwent treatment for a ruptured AAA at the Clinic of Surgery in the University Hospital in Pilsen between 1 January 2005 and 31 December 2009. We collected data on the atmospheric pressure in this period from the Czech Hydrometeorological Institute in Pilsen. Results We did not find a significant difference in atmospheric pressure values between the days when the rupture occurred versus the other days ( p < 0.5888). Moreover, we did not find significant changes in the atmospheric pressure during the 48 h preceding the rupture (Student’s test p < 0.4434) versus the day of rupture or in the mean atmospheric pressure in that month. Conclusion These findings suggest that atmospheric pressure and its changes do not affect the pathogenesis of AAA rupture.